Targeting of p300/CREB Binding Protein Coactivators by Simian Virus 40 Is Mediated through p53 - Borger, Darrell R. (American Society for Microbiology, 2006)
The primary transforming functions of simian virus 40 large T antigen (SV40 LT) are conferred primarily through the binding and inactivation of p53 and the retinoblastoma family members. Normal p53 function requires an association with the CREB binding protein (CBP)/p300 coactivators, and a ternary complex containing SV40 LT, p53, and CBP/p300 has been identified previously. In this report, we have evaluated a secondary function of p53 bound to the SV40 LT complex in mediating the binding of human CBP/p300. We demonstrate that p53 associated with SV40 LT was posttranslationally modified in a manner consistent with the binding of CBP/p300. Furthermore, expression of SV40 LT induced the proportion of p53 phosphorylated on S15. An essential function for p53 in bridging the interaction between SV40 LT and CBP/p300 was identified through the reconstitution of the SV40 LT-CBP/p300 complex upon p53 reexpression in p53-null cells. In addition, the SV40 LT-CBP/p300 complex was disrupted through RNA interference-mediated depletion of endogenous p53. We also demonstrate that SV40 LT was acetylated in a p300- and p53-dependent manner, at least in part through the CH3 domain of p300. Therefore, the binding of p53 serves to modify SV40 LT by targeting CBP and p300 binding to direct the acetylation of SV40 LT.